Seasonal effect of brazilian propolis on Candida albicans and Candida tropicalis - Sforcin, J. M. [UNESP]; Fernandes Júnior, A. [UNESP]; Lopes, C. A. M. [UNESP]; Funari, S. R. C. [UNESP]; Bankova, V. (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 2001)
Recently, propolis has been attracting the attention of researchers due to various biological activities and therapeutic properties. In Brazil, propolis is produced all year long, so there may be some seasonal variations. This work was carried out in order to compare propolis collected during the four seasons by its in vitro antimicrobial activity on yeast pathogens isolated from human infections. Propolis was produced by africanized honeybees in Botucatu, São Paulo State, collected throughout a year and pooled by season. Hydroalcoholic solutions of propolis were prepared with each pool and diluted in agar, using serial concentrations of propolis from each pool. A determination of minimal inhibitory concentration (MIC) was performed. The results show that Candida tropicalis and Candida albicans were susceptible to low concentrations of propolis, the latter showing a higher susceptibility. No differences were seen in relation to seasonal effects in the minimal inhibitory concentration of propolis.
Keywords: propolis; season; Candida; antimicrobial activity